ARABIC LANGUAGE LEARNING CONCEPTS ACCORDING TO IBN KHALDUN AND AZHAR ARSYAD - Roji, Fatkhur (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2024)
Learning Arabic always presents something that needs to be studied in depth, so the researcher researched in depth the concept of learning Arabic. This is because there are many versions of the concept of learning Arabic, so the researcher formulated the problem of how the concept of learning Arabic according to Ibn Khaldun and Azhar Arsyad, with The aim of the research is to find out in detail the similarities and differences regarding the concept of learning Arabic according to the two figures, through library research analysis with a comparative approach which is intended to compare the concepts of learning Arabic between the two figures, using the documentation method, based on the researcher's analysis, it was found that the similarities are found in the discussion. About language itself, and agreed about language as a means of communication, and guidance for students, while the results of the analysis of the differences are in the readiness of students, and the experience of students in previous sciences that students have obtained, with these results the researcher concludes Ibn Khaldun is more selective in the concept of learning Arabic, in the sense that religious knowledge and Arabic should not be combined into one unit, while Azhar Arsyad is exactly the opposite of what Ibn Khaldun expressed, Azhar Arsyad is of the view that students must first know their background. Knowledge, whether it is related to religion or not, it certainly cannot be separated between Arabic language knowledge and religion